Draft Annual Plan 1993-94 Part-I Government of Arunachal Pradesh - Planning Commission (Planning Commission, 1993)
Arunachal Pradesh has undergone constitutional changes in its evolution to attain Statehood. the then North East Frontier Agency(N.E.F.A)came into being as a Union Territory from 20th January,1972. the territory was given Legislative status with effect from 15th Aug'1975. the Statehood was attained on 20th February, 1987.
Government of Arunachal Pradesh, Planning and Development Department